The first record of the alpheid shrimp Automate isabelae Ramos-Tafur, 2018 from Brazil (Decapoda: Caridea) - Anker, Arthur; Tavares, Marcos (Zootaxa, 2024)
The alpheid shrimp Automate isabelae Ramos-Tafur, 2018 was described based on material found in stomachs of the lane snapper Lutjanus synagris (L.) in the Florida Keys and south-western coast of Florida, USA (24°N). In the present study, A. isabelae is reported from Araçá Bay, São Sebastião, São Paulo, Brazil (23°S), the first time since its original description, representing the first record of the species for the south-western Atlantic. The colour pattern of A. isabelae is illustrated for the first time. The differentiating characters between A. isabelae and its presumed eastern Pacific sister species A. rugosa Coutière, 1902 are discussed.